MALARIA PADA ANAK DI DESA PAGAR DESA (PEMUKIMAN SUKU ANAK DALAM) DI KABUPATEN MUSI BANYUASIN PROPINSI SUMATERA SELATAN - Sitorus, Hotnida; Oktarina, Reni; Ambarita, Lasbudi P. (Badan Penelitian dan Pengembangan Kesehatan, 2011)
Research on the incidence of malaria in children in Pagar Desa village of Musi Banyuasin District have aim to highlight the incidence of malaria in children. The community in this village comprises several ethnic including Suku Anak Dalam. This study use cross sectional design. The data were collected from children ages 9 year old or below. Blood sample were taken from each child and followed by examination of hemoglobin and spleen. Interview to child?s mothers were conducted to determine behaviours of the children. Out of 114 blood films collected, 17 blood samples showed positive malaria microscopically. Approximately 85,1% of children examined had hemoglobin below normal and 13,2% categorized splenomegaly. Statistically there was a significant correlation between malaria cases in children and enlarged spleen. Result suggest a critical need for improving the knowledge of the mothers about the link between malaria and its risk factors.